The Satisfaction Level of Universiti Teknologi MARA Sarawak’s Staff towards University Environment - Sirat, Zahrah; Kipli, Nur Aida; Kuldip Singh,; Augustine, Elizabeth Caroline; Goh, Kelvin; Jusoff, Kamaruzaman (2009)
This paper presents findings of an empirical study that was designed to investigate the perception of staff towards the university environment (university climate). Furthermore, the study was designed to determine the nature of current university climate and explore differences between academic and non-academic staff. A questionnaire adapted from Personal Assessment of the University Climate Survey (PAUCS) was administered to 550 university staff. The findings reveal a favorable university climate and no significant differences were found between components of campus climate and gender and category of staff except for collaboration. The authors propose measures for improvement of university climate.